Early vs late new-onset atrial fibrillation in STEMI patients: pathophysiological mechanisms and relationship with in-hospital outcomes. (14th October 2021) - Biccire, F G; Cardillo, I; Chianta, V; Ferrari, I; Capone, S; De Luca, A C; Torromeo, C; Acconcia, M C; Tanzilli, G; Barilla, F; Pastori, D
Abstract: Background: New-onset atrial fibrillation (NOAF) represents the most common supraventricular arrhythmia in the setting of ST-elevation myocardial infarction (STEMI), with up to 21% patients affected. The occurrence of NOAF has clinical relevance as previous studies showed that atrial fibrillation (AF), whether pre-existent to the admission or newly developed during STEMI hospitalization, is associated with worse short- and long-term prognosis. More recently, two distinct phenotypes of NOAF have been described, such as early NOAF (EAF) for AF occurring within 24 h from STEMI, and late NOAF (LAF) for AF onset beyond 24h. The mechanisms underlying EAF or LAF are poorly described. Objective: To investigate atrial branches occlusion and EAF or LAF onset in STEMI patients undergoing primary percutaneous coronary intervention. Methods: Retrospective cohort study including 155 STEMI patients. Patients were divided into 3 groups: sinus rhythm (SR), EAF or LAF. Clinical characteristics, angiographic features including occlusion of atrial branches, namely ramus ostia cavae superioris (ROCS), atrio-ventricular node artery (AVNA), right intermediate atrial artery (RIAA) and left intermediate atrial artery (LIAA), were assessed (Figure 1). We also investigated in-hospital adverse events (AEs) and death. Results: Mean age was 63.8±11.9 years; 78.7% of men. NOAF was detected in 22 (14.2%) patients: 10 (6.4%) EAF and 12 LAF (7.7%). Compared to EAF, LAF patients were older (p=0.013), with higher GRACE risk score (p=0.014) and Killip class (p=0.015), depressed ejection fraction (p=0.007), elevated filling pressures (p=0.029), higher c-reactive protein (p=0.014) and more TIMI flow <3 (p=0.015). Compared to SR, EAF was associated with higher prevalence of occluded ROCS (p=0.010), AVNA (p=0.005) and RIAA (p<0.001) (Figure 2). Moreover, EAF patients had more frequently ≥2 diseased atrial branches than SR (19.5%, p<0.001) and LAF (25%, p<0.030) patients. In LAF patients, a higher incidence of AEs (p=0.019 vs SR; p=0.029 vs EAF) and death (p=0.004 vs SR) was found. Conclusions: The occlusion of atrial branches is associated with early but not late NOAF following STEMI. LAF patients had worse in-hospital AEs and mortality. Funding Acknowledgement: Type of funding sources: None.